(untitled) (Politeja, 2022)
SOME PROBLEMS ASSOCIATED WITH THE MAJORITY OF VOTES REQUIRED FOR AMENDING THE 1997 CONSTITUTION OF POLAND The aim of this paper is to supplement the findings made by the doctrine of constitutional law regarding the requirements of the majority of votes for amending the 1997 Constitution of Poland at the parliamentary stage of that procedure. The following issues will be analysed in particular: the significance of constitutional amendment rules in a democratic system of government and their impact on its rigidity and durability; the role of the quorum as a factor contributing to the majority of votes’ requirements and some political dilemmas associated with that matter; the reasons and consequences of adopting different levels of the majority of votes for amending the Constitution in the Sejm and the Senate and their relation to the form of the relationships between those chambers. Regulations regarding amending the 1997 Constitution of Poland will be presented against a background of contemporary constitutions of European states. The important interpretative context will be constituted by the issues of axiology of democracy, parliamentary bicameralism and legitimization of power.